The Meaning of the Lyrics of the Song Eling-Eling Umat: An Analytical Descriptive Study of the Manifestation of Submission and the Priority of Worship - Asep Firmansyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the meaning of the lyrics of the song